Preparation of a silver nanocluster fluorescent composite film and its application in the detection of heavy metals
By blending low-temperature evaporation self-assembly method of the combination of aldehyde-based nanocellulose, silver ammonia solution and glutathione and glucose solution, a silver nanocluster fluorescent composite membrane with strong fluorescence characteristics and good toughness was prepared, and the solution was solved. In the prior art, the fluorescence characteristics and insufficient film formation intensity of silver nanocluster micelles are maintained after film formation, and the efficient, rapid and visual detection effect is achieved when detecting heavy metal ions.
Patent Information
- Application Number
- CN202211266642.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-17
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2042-10-17
AI Technical Summary
The prior art is difficult to maintain the fluorescence characteristics of silver nanocluster micelles after film formation, and at the same time, the film formation strength and toughness are insufficient, resulting in technical difficulties in detecting heavy metal ions.
Silver nanocluster micelles were prepared by mixing aldehyde-based nanocellulose, silver ammonia solution and glutathione solution, and blending them with glucose solution for low-temperature evaporation and self-assembly to prepare a strong fluorescence characteristic and good toughness. Silver nanocluster fluorescent composite membrane.
It realizes efficient preparation of silver nanocluster fluorescent composite film, maintains its fluorescence characteristics, and enhances the strength and toughness of the film formation, and is suitable for the rapid detection of copper ions by semi-quantitative and visualization.
Smart Images

Figure CN115674739B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nano functional materials, and particularly relates to the preparation of a silver nano cluster fluorescent composite film and its application in detecting heavy metals. Background Art
[0002] Heavy metals include gold, silver, copper, iron, cadmium, mercury, lead, etc. Among them, copper ions are the most common in life. Copper ions are an indispensable trace element for the human body and an important component of proteins and enzymes. They are beneficial to catalyze the synthesis of hemoglobin. However, excessive intake of copper ions can lead to protein denaturation, causing complications such as hemolysis, hepatitis, convulsions and kidney failure, and in severe cases, death.
[0003] At present, the methods for detecting heavy metal ions include ultraviolet visible spectrophotometer, atomic absorption spectrometry, atomic fluorescence spectrometry, mass spectrometry, electrochemical method, X-ray fluorescence spectrometry, etc. However, most of these methods are expensive and time-consuming. Therefore, it is of great significance to choose a simple, cost-effective method to quickly detect heavy metal ions.
[0004] The fluorescence properties of composite membranes prepared by using silver nanocluster micelles are expected to be used for rapid detection of heavy metal ions (such as copper ions), reduce the workload of detection personnel, and facilitate timely grasp of changes in heavy metal ions in the environment. However, how to keep the fluorescence properties of silver nanocluster micelles unchanged after film formation, as well as the strength and toughness of the film, have always been technical difficulties. Therefore, the preparation and application of fluorescent composite membranes for semi-quantitative, visual and rapid detection of metal ions (such as copper ions) in water has become a current hot topic. Summary of the invention
[0005] The primary purpose of the present invention is to overcome the shortcomings and deficiencies of the prior art and to provide a method for preparing a silver nanocluster fluorescent composite film.
[0006] Another object of the present invention is to provide a silver nanocluster fluorescent composite film prepared by the method.
[0007] Another object of the present invention is to provide an application of the silver nanocluster fluorescent composite film.
[0008] The purpose of the present invention is achieved through the following technical solutions:
[0009] A method for preparing a silver nanocluster fluorescent composite film comprises the following steps:
[0010] (1) Preparation of silver nanocluster micelles
[0011] A solution of aldehyde-modified nanocellulose (as a mild reducing agent and stabilizer), a silver ammonia solution (as a silver source) and a glutathione solution (as a capping agent) are mixed and stirred to react to obtain silver nanocluster micelles; wherein the molar ratio of the aldehyde content of the aldehyde-modified nanocellulose, the silver ammonia complex ions in the silver source solution and the glutathione is 1:1-10:1-10;
[0012] (2) Preparation of silver nanocluster fluorescent composite film
[0013] The silver nanocluster micelles obtained in step (1) are uniformly mixed with a glucose solution having a concentration of 10 to 50% by mass, and evaporated and self-assembled at 20 to 50° C. to form a silver nanocluster fluorescent composite film.
[0014] The aldehyde content of the aldehyde-modified nanocellulose in step (1) is 2.75 to 8.55 mmol / g, and it is preferably prepared by the following method:
[0015] (I) Preparation of Nanocellulose
[0016] The plant fiber pulp is debonded by a pulper to obtain a cellulose suspension; the cellulose suspension is then subjected to a micronized pulping treatment to obtain a nanocellulose pulp; wherein the micronized pulping treatment conditions are: a disc grinding gap of -200 μm to 0 μm, and a cycle treatment of 8 to 15 times;
[0017] (II) Preparation of highly filamentous nanocellulose
[0018] The nanocellulose slurry obtained in step (I) is subjected to a wall-breaking treatment using a wall-breaking machine to make the fiber surface highly fibrillated and obtain highly fibrillated nanocellulose; wherein the conditions for the wall-breaking treatment are: a rotation speed of 200 to 1000 rpm and a time of 1 to 10 minutes;
[0019] (III) Preparation of aldehyde-modified nanocellulose
[0020] The periodate and the highly fibrous nanocellulose obtained in step (II) are mixed and added into water, and reacted with stirring at 30-80° C. in a protective gas atmosphere and away from light to obtain aldehyded nanocellulose.
[0021] The raw material of the plant fiber pulp in step (I) is one or more of coniferous wood, hardwood or grass plants; the plant fiber pulp is preferably bleached coniferous wood pulp board.
[0022] The size of the nanocellulose described in step (I) is: length ≤500μm, diameter ≤300nm; preferably: length 10-300μm, diameter 10-200nm; more preferably: length 10-100μm, diameter 10-200nm; further preferably: length 10μm, diameter 10nm.
[0023] The nanocellulose described in step (I) can be prepared by one or a combination of mechanical, chemical, and biological methods; preferably, it is prepared by mechanical method.
[0024] The time for the decomposition in step (I) is 1 to 2 hours, preferably 1 hour.
[0025] The concentration of the nanocellulose slurry in step (II) is 1-5% by mass, preferably 5% by mass.
[0026] The rotation speed of the cell wall breaking treatment in step (II) is 500-1500 rpm, preferably 1000 rpm.
[0027] The cell wall breaking treatment time in step (II) is 5 to 10 minutes, preferably 5 minutes.
[0028] The periodate described in step (III) is preferably sodium periodate.
[0029] The mass ratio of the sodium periodate to the highly fibrillated nanocellulose is 1 to 5:1, preferably 1 to 3:1, and more preferably 1.5:1.
[0030] In step (III), the total mass concentration of periodate and highly fibrillated nanocellulose in the reaction system is 1% by mass.
[0031] The rotation speed of the stirring reaction in step (III) is 100 to 1000 rpm, preferably 200 to 600 rpm.
[0032] The protective gas in step (III) is preferably nitrogen.
[0033] The temperature of the stirring reaction in step (III) is preferably 30-60°C.
[0034] The stirring reaction time in step (III) is 1 to 10 hours, preferably 4 to 7 hours.
[0035] The molar ratio of the aldehyde content in the highly aldehyde-modified nanocellulose, the silver ammonia complex ions in the silver ammonia solution, and the glutathione capping agent described in step (1) is preferably 1:1-5:1-5; more preferably 1:1-3:1-3; further preferably 1:1:1-2; and further preferably 1:1:2.
[0036] The concentration of the silver-ammine complex in the silver-ammine solution described in step (1) is 50 to 200 mmol / L, preferably 100 mmol / L.
[0037] The glutathione described in step (1) is at least one of reduced glutathione (G-SH) and oxidized glutathione (GSSG); preferably reduced glutathione (G-SH).
[0038] The concentration of glutathione in step (1) is 50-200 mmol / L, preferably 100 mmol / L.
[0039] The aldehyde content of the aldehyde-modified nanocellulose in step (1) is 50 to 200 mmol / L, preferably 100 mmol / L.
[0040] The rotation speed of the stirring reaction in step (1) is 200 to 1500 rpm, preferably 1000 rpm.
[0041] The stirring reaction time in step (1) is 1 to 24 hours, preferably 15 to 20 hours, and more preferably 18 hours.
[0042] The stirring reaction in step (1) can be carried out in the absence of light or in the absence of light; preferably, the reaction is carried out in the absence of light.
[0043] The volume ratio of the glucose solution to the silver nanocluster micelles in step (2) is 1:10-40; more preferably 1:10-30; further preferably 1:20-30; further preferably 1:20.
[0044] The concentration of the glucose solution in step (2) is preferably 50% by mass.
[0045] The evaporation temperature in step (2) is preferably 35-50°C.
[0046] The evaporation time in step (2) is 1 to 24 hours, preferably 24 hours.
[0047] A silver nanocluster fluorescent composite film is prepared by any of the methods described above.
[0048] The silver nanocluster fluorescent composite film is used in detecting heavy metal ions and / or preparing materials with luminescent properties.
[0049] The heavy metal ions are one or more of gold, silver, copper, iron, cadmium, mercury and lead ions; preferably copper ions (the thiol functional group on GSH binds to Cu 2+ Highly coordinated).
[0050] The material with luminescent property can be used for detecting heavy metal ions.
[0051] A semi-quantitative and visual detection method for copper ions (Cu 2+ ) content, comprising the following steps:
[0052] (i) preparing at least three standard copper ion solutions with different concentration gradients, and then immersing the silver nanocluster fluorescent composite film in the standard copper ion solutions respectively, observing the color change of the silver nanocluster fluorescent composite film after immersion under ultraviolet light, taking pictures, and then determining the grayscale values of the obtained pictures respectively, and taking the average value to obtain the average grayscale value K;
[0053] (ii) constructing a linear relationship according to the average gray value K and the concentration of the standard copper ion solution to obtain a standard curve;
[0054] (iii) immersing the silver nanocluster fluorescent composite film into the sample to be tested, taking a photo, determining the grayscale value of the obtained photo, and taking the average value to obtain the average grayscale value K′; finally, calculating the concentration and / or content of copper ions in the sample to be tested based on the average grayscale value K′ and the standard curve.
[0055] The gray value of the silver nanocluster fluorescent composite film in the present invention in pure water (0 mol / L solution) under ultraviolet light is 0, and the copper ion concentration can be roughly estimated based on the change of the bright red fluorescence of the fluorescent composite film.
[0056] The concentration of the standard copper ion solution described in step (i) is 0 to 800 nmol / L.
[0057] The wavelength of the ultraviolet lamp described in step (i) is 365nm.
[0058] The grayscale value of the photo in step (i) can be determined by Photoshop software (PS software).
[0059] Compared with the prior art, the present invention has the following advantages and effects:
[0060] (1) The present invention treats the nanocellulose treated with ultrafine particles with a wall breaking machine to make the fiber surface highly fibrillated, and then further performs an aldehyde treatment to obtain nanofibers with a high aldehyde content; then, the oxidized nanocellulose rich in aldehyde groups is used as a mild reducing agent and stabilizer, and glutathione is used as a capping agent to prepare silver nanocluster micelles by a simple room temperature high-speed stirring method, and then the micelles are blended with a glucose solution for low-temperature evaporation self-assembly to prepare a fluorescent composite film. The preparation process is green, simple, and environmentally friendly. Under ultraviolet light and observed against a black background, the silver nanocluster composite film exhibits strong red fluorescence.
[0061] (2) The present invention enhances the toughness of the fluorescent composite film after drying by mixing glucose solution and silver nanocluster micelles at low temperature, and maintains the fluorescent properties of the silver nanocluster fluorescent composite film.
[0062] (3) In the present invention, the carboxyl groups formed by oxidation of the aldehyde groups on the nanocellulose after participating in the reaction can play a good stabilizing role on the silver nanocluster micelles. The addition of glucose solution is also beneficial to the formation of the silver nanocluster fluorescent composite film. At the same time, this method also avoids the addition of highly toxic reducing agents such as the commonly used sodium borohydride, and also avoids the use of strong base NaOH, and the reaction is controllable and highly repeatable.
[0063] (4) The present invention performs surface modification on nanocellulose, a green, degradable and widely available natural polymer material, to give it reducing aldehyde groups at the C-2 and C-3 positions. Through a simple silver mirror reaction, the controllable preparation of silver nanocluster micelles can be achieved under the stabilization of glutathione and aldehyde-modified nanocellulose. The large-scale preparation of silver nanocluster fluorescent composite membranes is achieved by adding glucose solution and self-assembly by low-temperature evaporation. The silver nanocluster fluorescent composite membrane has a high sensitivity response to copper ions and can be used for semi-quantitative and visual detection of copper ions. The detection process is simple and rapid. The average gray value can be determined by PS software to construct a fluorescent sensing system for detecting copper ions. The invention has broad application prospects and market value in the semi-quantitative and visual rapid detection of copper ions. BRIEF DESCRIPTION OF THE DRAWINGS
[0064] Figure 1 This is a transmission electron microscopy image of the silver nanocluster micelles prepared in Example 4 of the present invention.
[0065] Figure 2 These are actual pictures of the silver nanocluster fluorescent composite film prepared in Example 4 of the present invention under natural light and ultraviolet light; wherein, (a) is the actual picture under natural light; and (b) is the actual picture under ultraviolet light.
[0066] Figure 3These are pictures of the silver nanocluster fluorescent composite film prepared in Example 4 of the present invention under different copper ion concentrations and ultraviolet light; wherein, (a), (b), (c) and (d) are pictures of the silver nanocluster fluorescent composite film at copper ion concentrations of 0, 200, 500, and 800 nmol / L (all under ultraviolet light), respectively.
[0067] Figure 4 4 is a relationship diagram between the average gray value K of the silver nanocluster fluorescent composite film prepared in Example 4 of the present invention at different copper ion concentrations and the corresponding copper ion concentration. DETAILED DESCRIPTION
[0068] The present invention is further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art. The test methods for which specific experimental conditions are not specified in the following examples are usually in accordance with conventional experimental conditions. Unless otherwise specified, the reagents and raw materials used in the present invention can be obtained commercially.
[0069] The aldehyde-modified nanocellulose involved in the embodiments of the present invention is prepared by the following method:
[0070] (1) Soak a bleached coniferous wood pulp board (purchased from Hubei Chemical Fiber Development Co., Ltd.) in water for 24 hours, and use a Wall-E pulper to beat it for 1 hour (with an additional 1 kg weight (weight)) to obtain a cellulose suspension (5 wt%); then, the cellulose suspension is subjected to micronization refining treatment using an ultrafine refiner, wherein the disc refiner gap is -, and the treatment is circulated for 8 to 15 times to obtain the nanocellulose (length 20 μm, diameter 10 nm).
[0071] (2) the nanocellulose treated with ultrafine particles in step (1) is subjected to a wall breaking treatment using a wall breaking machine, wherein the concentration of the nanocellulose is controlled to be 2 wt %, the speed is controlled to be 200 to 1000 rpm (preferably 1000 rpm), and the time is 1 to 10 min (preferably 5 min), so that the fiber surface is highly fibrillated;
[0072] (3) Aldehyde modification: Sodium periodate and highly filamentized mechanical nanocellulose (the mass ratio of periodate to nanocellulose is 1.5:1) are mixed and added to water (the reaction concentration of the dispersion of periodate and highly filamentized nanocellulose added to water is preferably 1 wt%), and the reaction is stirred at 30-80°C (45°C in this experiment), protected from light, and with N2 protection (speed 200-600 rpm, time 4-7 h) to obtain aldehyde-rich nanocellulose at the C-2 and C-3 sites (aldehyde content of 2.75-8.55 mmol / g).
[0073] The glutathione involved in the embodiments of the present invention is reduced glutathione (G-SH).
[0074] The fluorescence intensity involved in the examples of the present invention was measured by a fluorescence spectrometer (three replicates were set).
[0075] Example 1
[0076] At room temperature, 5 mL of 0.1 mol / L silver ammonia solution, 5 mL of 0.1 mol / L glutathione aqueous solution and 5 mL of 0.1 mol / L aldehyded nanocellulose solution were mixed, and an appropriate amount (5 mL) of pure water was added. After magnetic stirring for 18 h at room temperature (speed of 1000 rpm), silver nanocluster micelles were obtained. The fluorescence emission peak of the silver nanocluster micelles is around 592 nm. Under ultraviolet light (365 nm, 12 W), when observed against a black background, it exhibits weak orange fluorescence with a fluorescence intensity of 4.50×10 4 Then, 0.5 mL of glucose solution (concentration of 50 wt%) was added and ultrasonically dispersed for 5 min, and then placed in an evaporating dish and dried at 50°C for 24 h. The dried fluorescent composite film (thickness 19 μm) emitted a weak orange fluorescence under an ultraviolet lamp (365 nm, 12 W).
[0077] Example 2
[0078] At room temperature, 5 mL of 0.1 mol / L silver ammonia solution, 10 mL of 0.1 mol / L glutathione aqueous solution and 5 mL of 0.1 mol / L aldehyded nanocellulose solution were mixed, and an appropriate amount (5 mL) of pure water was added. After magnetic stirring for 18 h at room temperature (speed of 1000 rpm), silver nanocluster micelles were obtained. The fluorescence emission peak of the silver nanocluster micelles is around 592 nm. Under ultraviolet light (365 nm, 12 W), when observed against a black background, orange fluorescence is presented, and the fluorescence intensity is 6.80×10 4 Then, 0.5 mL of glucose solution (concentration of 50 wt%) was added and ultrasonically dispersed for 5 min, and then placed in an evaporating dish and dried at 50°C for 24 h. The dried fluorescent composite film (thickness 19 μm) emitted a weak orange fluorescence under an ultraviolet lamp (365 nm, 12 W).
[0079] Example 3
[0080] At room temperature, 5 mL of 0.1 mol / L silver ammonia solution, 10 mL of 0.1 mol / L glutathione aqueous solution and 5 mL of 0.1 mol / L aldehyded nanocellulose solution were mixed, and an appropriate amount (5 mL) of pure water was added. After magnetic stirring for 18 h at room temperature (speed of 1000 rpm), silver nanocluster micelles were obtained. The fluorescence emission peak of the silver nanocluster micelles is around 592 nm. Under ultraviolet light (365 nm, 12 W), when observed against a black background, orange fluorescence is presented, and the fluorescence intensity is 6.80×10 4 Then, 1 mL of glucose solution (concentration of 50 wt%) was added and ultrasonically dispersed for 5 min, and then placed in an evaporating dish and dried at 50°C for 24 h. The dried fluorescent composite film (thickness 19 μm) emitted orange fluorescence under ultraviolet light (365 nm, 12 W).
[0081] Example 4
[0082] (1) 5 mL of 0.1 mol / L silver ammonia solution, 10 mL of 0.1 mol / L glutathione aqueous solution and 5 mL of 0.1 mol / L aldehyded nanocellulose solution were mixed at room temperature, and an appropriate amount (5 mL) of pure water was added. After magnetic stirring at room temperature for 18 h (rotation speed was 1000 rpm), silver nanocluster micelles were obtained. The fluorescence emission peak of the silver nanocluster micelles was around 592 nm. When observed under ultraviolet light (365 nm, 12 W) against a black background, orange fluorescence was observed with a fluorescence intensity of 6.80×10 4 Then, 1 mL of glucose solution (concentration of 50 wt%) was added and ultrasonically dispersed for 5 min, and then placed in an evaporating dish and dried at 35°C for 24 h. The dried silver nanocluster composite film (thickness 19 μm) emitted bright red fluorescence under ultraviolet light (365 nm, 12 W).
[0083] (2) The silver nanocluster micelles prepared in step (1) are dispersed in an aqueous solution according to a certain ratio (dispersed according to a concentration gradient so that the silver nanoclusters can be observed under an electron microscope), and then dropped onto an ultrathin carbon film (the ultrathin carbon film is purchased from Zhongjing Keyi Membrane Technology Co., Ltd., model number BZ11033b). After vacuum drying, a transmission electron microscope test is performed to measure the particle size of the silver nanoclusters to be 1 to 5 nm. Figure 1 The actual pictures of silver nanocluster fluorescent composite film under natural light and ultraviolet light are shown in Figure 2 Shown: From Figure 2 It can be seen that the color of the silver nanocluster micelles after film formation is dark brown and appears bright red under ultraviolet light.
[0084] (3) The silver nanocluster composite film prepared in this example was immersed in copper chloride solutions of different known concentrations (0, 200, 500, 800 nmol / L) and photographed and observed under ultraviolet light after 10 seconds ( Figure 3 ), the grayscale values of the composite films at different concentrations can be determined by PS software, and the determination model can be constructed by the corresponding grayscale values and copper ion concentrations ( Figure 4 ).
[0085] Comparative Example 1
[0086] At room temperature, 5 mL of 0.1 mol / L silver ammonia solution, 2.5 mL of 0.1 mol / L glutathione aqueous solution and 5 mL of 0.1 mol / L aldehyded nanocellulose solution were mixed, and an appropriate amount (5 mL) of pure water was added. After magnetic stirring for 18 h at room temperature (speed of 1000 rpm), silver nanocluster micelles were obtained. The fluorescence emission peak of the silver nanocluster micelles is around 590 nm. Under ultraviolet light (365 nm, 12 W), when observed against a black background, it exhibits weak orange fluorescence with a fluorescence intensity of 1.08×10 4 Then, 0.5 mL of glucose solution (concentration of 50 wt%) was added and ultrasonically dispersed for 5 min, and then placed in an evaporating dish and dried at 50° C. for 24 h. The dried composite film (thickness 19 μm) appeared black under ultraviolet light (365 nm, 12 W).
[0087] Comparative Example 2
[0088] At room temperature, 5 mL of 0.1 mol / L silver ammonia solution and 5 mL of 0.1 mol / L aldehyded nanocellulose solution were mixed, and an appropriate amount (5 mL) of pure water was added. After magnetic stirring for 18 h (rotation speed was 1000 rpm) at room temperature, micelles were obtained. The non-fluorescent emission peak of the cluster micelles did not show fluorescence when observed under ultraviolet light (365 nm, 12 W) and black background. Subsequently, 1 mL of glucose solution (concentration was 50 wt%) was added and ultrasonically dispersed for 5 min, and placed in an evaporating dish and dried at 35 ° C for 24 h. The dried composite film (thickness 19 μm) was black under ultraviolet light (365 nm, 12 W).
[0089] Comparative Example 3
[0090] At room temperature, 5 mL of 0.1 mol / L silver ammonia solution and 10 mL of 0.1 mol / L glutathione aqueous solution were mixed, and an appropriate amount (5 mL) of pure water was added. After magnetic stirring for 18 h (rotation speed was 1000 rpm) at room temperature, micelles were obtained. The non-fluorescent emission peak of the cluster micelles did not show fluorescence when observed under ultraviolet light (365 nm, 12 W) and black background. Subsequently, 1 mL of glucose solution (concentration was 50 wt%) was added and ultrasonically dispersed for 5 min, and placed in an evaporating dish and dried at 35 ° C for 24 h. The dried composite film was black under ultraviolet light (365 nm, 12 W).
[0091] Comparative Example 4
[0092] At room temperature, 5 mL of 0.1 mol / L silver ammonia solution, 10 mL of 0.1 mol / L glutathione aqueous solution and 5 mL of 0.1 mol / L aldehyded nanocellulose solution were mixed, and an appropriate amount (5 mL) of pure water was added. After magnetic stirring for 18 h at room temperature (speed of 1000 rpm), silver nanocluster micelles were obtained. The fluorescence emission peak of the silver nanocluster micelles is around 592 nm. Under ultraviolet light (365 nm, 12 W), when observed against a black background, orange fluorescence is presented, and the fluorescence intensity is 6.80×10 4 Then, 1 mL of glucose solution (concentration of 50 wt%) was added and ultrasonically dispersed for 5 min, and then placed in an evaporating dish and dried at 105°C for 24 h. The dried composite film (thickness 19 μm) appeared black under ultraviolet light (365 nm, 12 W).
[0093] Comparative Example 5
[0094] At room temperature, 5 mL of 0.1 mol / L silver ammonia solution, 10 mL of 0.1 mol / L glutathione aqueous solution and 5 mL of 0.1 mol / L aldehyded nanocellulose solution were mixed, and an appropriate amount (5 mL) of pure water was added. After magnetic stirring for 18 h at room temperature (speed of 1000 rpm), silver nanocluster micelles were obtained. The fluorescence emission peak of the silver nanocluster micelles is around 592 nm. Under ultraviolet light (365 nm, 12 W), when observed against a black background, orange fluorescence is presented, and the fluorescence intensity is 6.80×10 4 Place in an evaporating dish and dry at 35°C for 24 hours. The dried composite film (thickness 19 μm) exhibits weak orange fluorescence under ultraviolet light (365 nm, 12 W), and the composite film is prone to cracking due to drying.
[0095] Comparative Example 6
[0096] At room temperature, 5 mL of 0.1 mol / L silver ammonia solution, 10 mL of 0.1 mol / L L-penicillamine aqueous solution and 5 mL of 0.1 mol / L aldehyded nanocellulose solution were mixed, and an appropriate amount (5 mL) of pure water was added. After magnetic stirring for 18 h at room temperature (speed of 1000 rpm), silver nanocluster micelles were obtained. The fluorescence emission peak of the silver nanocluster micelles is around 576 nm. Under ultraviolet light (365 nm, 12 W), when observed against a black background, orange fluorescence is presented, and the fluorescence intensity is 4.77×10 4 Then, 1 mL of glucose solution (concentration of 50 wt%) was added and ultrasonically dispersed for 5 min, and then placed in an evaporating dish and dried at 35°C for 24 h. The dried composite film (thickness 19 μm) showed weak orange fluorescence under ultraviolet light (365 nm, 12 W).
[0097] For the convenience of comparison, the above Examples 1 to 4 and Comparative Examples 1 to 6 are listed in the form of Table 1:
[0098] Table 1
[0099]
[0100] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a silver nanocluster fluorescent composite film, characterized in that: The steps include: (1) Preparation of silver nanocluster micelles The aldehyde-modified nanocellulose solution, the silver-ammonia solution and the glutathione solution are mixed and stirred to react fully to obtain silver nanocluster micelles; wherein the molar ratio of the aldehyde content of the aldehyde-modified nanocellulose, the silver-ammonia complex ions in the silver-ammonia solution and the glutathione is 1:1-10:1-10; (2) Preparation of silver nanocluster fluorescent composite film The silver nanocluster micelles obtained in step (1) are evenly mixed with a glucose solution having a concentration of 10-50% by mass, and evaporated and self-assembled at 20-50° C. to form a silver nanocluster fluorescent composite film.
2. The method for preparing the silver nanocluster fluorescent composite film according to claim 1, characterized in that: The molar ratio of the aldehyde content of the aldehyde-modified nanocellulose, the silver-ammonia complex ions in the silver-ammonia solution, and glutathione is 1:1-5:1-5; The glutathione in step (1) is at least one of reduced glutathione and oxidized glutathione; The volume ratio of the glucose solution to the silver nanocluster micelles in step (2) is 1:10-40; The concentration of the glucose solution in step (2) is 50% by mass; The evaporation temperature in step (2) is 35-50°C; The evaporation time in step (2) is 1 to 24 hours.
3. The method for preparing the silver nanocluster fluorescent composite film according to claim 2, characterized in that: The molar ratio of the aldehyde content of the aldehyde-modified nanocellulose, the silver-ammonia complex ions in the silver-ammonia solution, and glutathione is 1:1:2; The glutathione described in step (1) is reduced glutathione; The volume ratio of the glucose solution to the silver nanocluster micelles in step (2) is 1:20; The evaporation time in step (2) is 24 hours.
4. The method for preparing the silver nanocluster fluorescent composite film according to claim 1, characterized in that: The aldehyde content of the aldehyde-modified nanocellulose in step (1) is 2.75-8.55 mmol / g, and the aldehyde-modified nanocellulose is prepared by the following method: (I) Preparation of Nanocellulose The plant fiber pulp is debonded by a pulper to obtain a cellulose suspension; the cellulose suspension is then subjected to a micro-refining treatment to obtain a nanocellulose pulp; wherein the micro-refining treatment conditions are: a disc grinding gap of -200 µm to 0 µm, and a cycle treatment of 8 to 15 times; (II) Preparation of highly filamentous nanocellulose The nanocellulose slurry obtained in step (I) is subjected to a wall-breaking treatment using a wall-breaking machine to make the fiber surface highly fibrillated and obtain highly fibrillated nanocellulose; wherein the conditions for the wall-breaking treatment are: a rotation speed of 200-1000 rpm and a time of 1-10 min; (III) Preparation of aldehyde-modified nanocellulose Mixing periodate and the highly fibrous nanocellulose obtained in step (II) and adding them to water, stirring and reacting in a protective gas atmosphere at 30-80° C. in the dark to obtain aldehyde-modified nanocellulose; The raw material of the plant fiber slurry in step (I) is one or more of coniferous wood, hardwood or grass plants; The size of the nanocellulose in step (I) is: length ≤ 500 µm, diameter ≤ 300 nm; The time for decomposition in step (I) is 1 to 2 hours; The concentration of the nanocellulose slurry in step (II) is 1 to 5% by mass; The rotation speed of the cell wall breaking treatment in step (II) is 500-1500 rpm; The cell wall breaking treatment in step (II) takes 5 to 10 minutes; The periodate described in step (III) is sodium periodate; The mass ratio of the sodium periodate to the highly fibrillated nanocellulose is 1-5:1; In step (III), the total mass concentration of periodate and highly fibrillated nanocellulose in the reaction system is 1% by mass; The stirring reaction in step (III) is carried out at a speed of 100 to 1000 rpm; The stirring reaction time in step (III) is 1 to 10 h.
5. The method for preparing the silver nanocluster fluorescent composite film according to claim 1, characterized in that: The concentration of silver ammonia complex ions in the silver ammonia solution described in step (1) is 50-200 mmol / L; The concentration of glutathione in step (1) is 50-200 mmol / L; The aldehyde content of the aldehyde-modified nanocellulose in step (1) is 50-200 mmol / L; The stirring reaction in step (1) is carried out at a speed of 200 to 1500 rpm; The stirring reaction time in step (1) is 1 to 24 h.
6. A silver nanocluster fluorescent composite film, characterized in that: It is prepared by the method according to any one of claims 1 to 5.
7. Use of the silver nanocluster fluorescent composite film according to claim 6 in detecting heavy metal ions or preparing materials with luminescent properties.
8. The use according to claim 7, characterized in that: The heavy metal ions are one or more of gold, silver, copper, iron, cadmium, mercury and lead ions.
9. A method for semi-quantitative and visual detection of copper ion content, characterized in that: The steps include: (i) preparing at least three standard copper ion solutions with concentration gradients, and then immersing the silver nanocluster fluorescent composite film according to claim 6 in the standard copper ion solutions respectively, observing the color change of the silver nanocluster fluorescent composite film after immersion under ultraviolet light, taking pictures, and then determining the grayscale values of the obtained pictures respectively, and taking the average value to obtain the average grayscale value K; (ii) constructing a linear relationship based on the average gray value K and the concentration of the standard copper ion solution to obtain a standard curve; (iii) immersing the silver nanocluster fluorescent composite film as described in claim 6 into a sample to be tested, taking a photo, determining the grayscale value of the obtained photo, and taking the average value to obtain an average grayscale value K′; finally, calculating the concentration and / or content of copper ions in the sample to be tested based on the average grayscale value K′ and the standard curve.
10. The method according to claim 9, characterized in that: The concentration of the standard copper ion solution in step (i) is 0 to 800 nmol / L; The wavelength of the ultraviolet lamp in step (i) is 365 nm; The grayscale value of the photograph in step (i) is determined by Photoshop software.
Citation Information
Patent Citations
Preparation method of silver-loaded nano cellulose-chitosan composite film
CN106832437A
Nanocellulose-based fluorescent silver nanocluster as well as preparation method and application thereof
CN114523123A